ANALISA PERBEDAAN COVID-19 TERHADAP RISK & RETURN SAHAM SEKTOR TRANSPORTASI YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2017 - 2021 - Afriando; Melinda Malau; Tarigan, Lukas (Buletin Ekonomi, 2023)
The purpose of this study was to analyze the difference in risk and return in the transportation sector during the Covid-19 pandemic. The research method used was quantitative, namely determining stock prices before Covid-19 and during Covid-19. Systematic and unsystematic risks and market equilibrium models are verified using the CAPM method. This article is expected to increase individual and investor knowledge in predicting profits and losses in investing. The results of the study show that there is no significant difference between stock returns in the transportation sector from 2017 to 2021 before and during the COVID-19 pandemic. The hypothesis is supported by the data, with the paired t test producing significant results sig (2-tailed) > α value of 0.034 > 0.05. The stock returns in the transportation sector were not much different before and after the COVID-19 pandemic. In addition, there was no significant difference between stock risk in the transportation sector from 2017 to 2021 before and during the COVID-19 pandemic. The results of the paired t test with a sig (2-tailed) value > α value of 0.029 > 0.05 are used to support the conclusion that the hypothesis is supported. Keywords: COVID-19, transportation, stock exchange